Interferência da poda de ramos primários e armazenamento sobre frutos e sementes de mogango (Cucurbita pepo L.). - Malone, Paula Fernanda Vaz de Ávila (2008)
This work comprised two experiments, the first of which aimed to assess the effect of pruning on production, fruit morphology and physiological quality of squash seeds. In the field the experiment was displayed as T1 (no pruning of primary branches) and T2 (pruning of main branches). For both experiments the female flowers were tagged 30, 35, 40 and 45 days after anthesis and their fruits harvested at each date. For each fruit age three parameters were measured: total number of fruits, morphology () and number of seeds per fruit and their dry weight. To assess seed quality the following parameters were considered: moisture, total germination, first count germination, accelerated ageing, field emergence and seed dry weight. The results showed that the initial moisture content was extremely high but decreased through the subsequent maturation stages at 40%. Pruning of primary branches did not increase the number of fruits or had any effects on the morphological quality (length, diameter, pulp thickness) of fruits and seeds (germination, field emergence and seed dry weight), since for the majority of the parameters evaluated T1 out yielded T2. The objective of the second experiment was to evaluate the influence of age and post harvest storage of fruits on the physiological quality of squash seeds. To this purpose the fruits were harvested on four different dates after anthesis: 35, 40, 45 and 50 days and stored for 0, 20, 40 and 60 days. Seeds were analyzed for moisture, total germination, first count germination, accelerated ageing, field emergence and seed dry weight. The length of the storage period improved the seed quality of fruits harvested at early stages (35 to 40 days post-anthesis), but a storage period of at least 20 days post-harvest are needed to obtain seeds of high quality.